Use cases for Blockchain in the Energy Industry Opportunities of emerging business models and related risks. (November 2019) - Bürer, Mary Jean; de Lapparent, Matthieu; Pallotta, Vincenzo; Capezzali, Massimiliano; Carpita, Mauro
Highlights: Drivers for blockchain use cases in the energy industry. Review of existing use cases across countries and across incumbents as well as start-ups active in the energy industry. Risks including regarding electric power exchange related to the application of blockchain in the energy sector. Assessment of opportunities for sustainability from blockchain, including in developing countries. Abstract: This paper focuses on use cases for blockchain architectures with the goal of identifying major issues to study further in future research works. The paper will also consider aspects related to energy consumption of blockchain architectures, and risks and opportunities of emerging business models while ensuring a reliable distribution network and security of supply.